Keefektifan model pembelajaran problem-based learning berbasis literasi terhadap pemecahan masalah siswa MI Al Mustajab - Kayniya, Marshanda Shawma; Putra, Lisa Virdinarti (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2024)
This research aims to determine the effectiveness of the Literacy-based Problem Based Learning (PBL) learning model in solving problems for MI Al Mustajab students. This type of research is a quasi-experimental design in the form of the non-equivalent group design. The population in this research are all MI Al Mustajab students. The sampling technique uses a non-probability sampling technique which is taken by purposive sampling. The research sample was class IIA and IIB MI Al Mustajab. Data collection techniques in this research are test and non-test techniques. The test technique uses pretest and posttest while the non-test technique uses observation, questionnaires and documentation. Data analysis techniques include normality test, homogeneity test, one way anova test, simple linear regression test, independent sample t test and paired sample t test. The results of the research show: (1) There is an influence of the use of the literacy-based Problem Based Learning (PBL) learning model on problem solving abilities, as evidenced by a significance level of 0.000 <0.05 using a simple linear regression test (2) There are differences in students' abilities regarding the use of the learning model Literacy-based Problem Based Learning (PBL), proven by a significance level of 0.016 < 0.05 using the independent sample t test (3). The literacy-based Problem Based Learning (PBL) learning model is able to improve problem solving abilities, proven by a significance level of 0.000 < 0.05 using the paired sample t test. The conclusion of this research is that the literacy-based Problem Based Learning (PBL) learning model is effective in students' conceptual understanding abilities. Keywords: Problem Based Learning (PBL); Literacy; Problem Solving